Phospholipase A2 in skin biology: new insights from gene-manipulated mice and lipidomics - Makoto Murakami; Kei Yamamoto; Yoshitaka Taketomi (BMC, 2018)
Abstract The skin represents one of the tissues that are most profoundly influenced by alterations in the quality of lipids (lipoquality). Lipids not only constitute cellular membranes, but also serve as bioactive lipid mediators and essential components of the skin barrier. Phospholipase A2 (PLA2) enzymes supply fatty acids and lysophospholipids from membrane phospholipids, thereby variably affecting cutaneous homeostasis. Accordingly, perturbation of particular PLA2-driven lipid pathways can be linked to various forms of skin disease. In this review article, we highlight the roles of several PLA2 subtypes in cutaneous pathophysiology, as revealed by transgenic/knockout studies in combination with comprehensive lipidomics. We focus mainly on secreted PLA2 group IIF (sPLA2-IIF), which is associated with epidermal hyperplasia through mobilization of a unique lipid metabolite. We also address the distinct roles of sPLA2-IIE in hair follicles and sPLA2-IID in lymphoid immune cells that secondarily affect cutaneous inflammation, and provide some insights into species differences in sPLA2s. Additionally, we briefly overview the patatin-like phospholipase PNPLA1, which belongs to the Ca2+-independent PLA2 (iPLA2) family, as a key regulator of skin barrier function through catalysis of a unique non-PLA2 reaction. These knowledges on lipid metabolism driven by various PLA2 subtypes will open novel opportunities for translated studies toward diagnosis and therapy of human skin diseases.